PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN BERBASIS PENDEKATAN ACCELERATED LEARNING DI KELAS V SD NEGERI 011 AIR EMAS KECAMATAN SINGINGI - Tati Nurhayati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by the number of students experiencing difficulties in reading comprehension learning. The purpose of this study is to improve students' reading comprehension skills. The approach used in this study uses an accelerated learning approach. This research is a classroom action research consisting of II cycles with research subjects of class V SD Negeri 011 Air Emas. The results showed, the assessment of the process of reading skills of students for each assessment indicator was in the value range of 78.35% up to 87.35% which was included in the good and very good category. While the results of the assessment of the overall reading skills process were 82.32% with a very good category. Based on the results of these studies it can be concluded that learning based on the accelerated learning approach can enhance reading comprehension skills of students in class V 011 Air Emas Elementary School, Singingi District